Development of 'halal' verification and tracking system with augmented reality (AR) technology for 'halal' certified restaurants in Brunei Darussalam - Pg Hj Metussin, Ak Mohd Syukri; Deuraseh, Nurdeng @ Nurdeen (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Brunei Darussalam government is putting in efforts to ensure every Muslims regardless citizens or tourists to be well informed on “Halalan Toyyiban” food and beverages. As ‘Halal’ is a priority for all Muslims, the abused of ‘Halal’ word equally misused by Muslims and Non-Muslims is not to be addressed lightly. Therefore, in order to provide solutions for the issues, a study is conducted with primary objectives to identify ‘Halal’ certified restaurants in Brunei Darussalam and to develop a prototype of ‘Halal’ Verification System using Augmented Reality (AR) Technology. A list of ‘Halal’ certified restaurants is obtained from Brunei Halal Food Council that is utilized as a guideline for conducting observation and questionnaire survey on every ‘Halal’ certified restaurant along with its coordinates in Brunei Darussalam. Augmented Reality feature within Android environment is the basis for the proof of concept. An informative, user friendly and interactivity are the main features of the application that functions mainly to identify ‘Halal’ certified restaurants within user current location. Tests are made with 10 users of smart phone in locating nearest ‘Halal’ certified restaurants. 107 ‘Halal’ certified restaurants in Brunei Darussalam are used as the data set for the prototype’s application development. All tests using the prototype’ application is proven success with users able to locate ‘Halal’ certified restaurants and information pertaining to it. This is aims to promote Brunei Darussalam image as a Muslim’s country as well as Islam as a way of life is further promote.